The transbronchial ultrasound in diagnostics of respiratory system diseases - Piorunek, Tomasz; Skowronek, Janusz; Nowicka, Agata; Goździk, Joanna; Batura-Gabryel, Halina; Młynarczyk, Witold (Contemporary Oncology/Współczesna Onkologia, 2005)
Transbronchial ultrasound (TBUS) is an invasive technique, which is complementary to fiberoptic bronchoscopy and computed tomography in the diagnostics of chest diseases. During more than ten years of TBUS evolution, the device and technique improved, the range of indications expanded. The ultrasound device consists of a 20MHz probe used with a saline solution-filled balloon tip catheter. Circumferential contact of the balloon transducer to the bronchial wall is essential to create a 360-degree cross-sectional view of the airway and adjacent mediastinal structures. The 2.5-3.2 mm ultrasound catheter is passed through the working channel of the fiberoptic bronchoscope to the area of interest. The image-depth range varies from 1.5 to 12 cm, and the image diameter is 3 to 9 cm, depending on the probe utilised. Indications for TBUS include: assistance for more accurate staging of malignancy by determination of the depth of tumour invasion in tracheobronchial disease; depth of hilar disease invasion of the pulmonary vasculature; and disease involvement to paratracheal/parabronchial sites. TBUS may assist with the diagnostic yield of transbronchial needle aspiration; assess the extent of disease to assist in selecting the most appropriate therapy, such as stent placement, electrocautery or photodynamic therapy, and identify and characterise peripheral pulmonary lesions. Contraindications to TBUS are the same as to standard fibreoptic bronchoscopy. The method appears to be well tolerated by the patient and adds approximately 10 minutes to a standard fiberoptic bronchoscopy [1]. The aim of this study was to introduce a current opinion on TBUS possibilities and limitations in the diagnostics of lung cancer and other respiratory system diseases.